Effects of green transformational leadership on green performance of employees via the mediating role of corporate social responsibility: Reflection from North Cyprus. (May 2022) - Tosun, Cevat; Parvez, M. Omar; Bilim, Yasin; Yu, Larry
Abstract: This study examined the mediator effect of corporate social responsibility (CSR) on the relationship between green transformational leadership (GTL) and green performance (GP) in restaurant management in North Cyprus. A sample of 292 employees in small and medium-sized restaurants was collected in four major cities in North Cyprus. Structural equation modeling was used to test the direct relationship between GTL and GP, and the mediated indirect relationship between GTL and GP. Results showed that CSR had a mediating effect on the relationship between GTL and GP, although there was no direct relationship between them. This study identified the critical linkage of CSR principles in connecting restaurant managers' GTL with organizational GP by employees (e.g., waste management, energy efficiency, local sourcing, reuse, and recycling) in ecologically sensitive island destinations. Theoretical and practical implications and suggestions for future research are discussed. Highlights: CSR can play a major role in developing green applications in island destinations.of Cyprus. GTL has an indirect effect on GP through the mediation of CSR. Leaders can support employee GP by embedding CSR concepts and principles in restaurant operations. Implementatiosn of GP by restaurant SMEs benefit the local environment and social well being.